Prevalence of Abnormal Pap Smear in Women Undergoing Liver Transplantation [15E]. (May 2017) - Threadcraft, Marcus; Guha, Paulami; Wells, Ali; Dinh, Tri; Nguyen, Justin; Harnois, Denise
Abstract : INTRODUCTION: Female patients being evaluated for liver transplantation (LT) routinely undergo a gynecologic exam including cervical cancer screening. The prevalence of cervical cytologic abnormalities in this high risk population is unknown. Our study determines prevalence of cervical cytologic abnormalities, HPV positive status, and risk factors for abnormal cervical screening for this population. METHODS: With Institutional review board approval, we reviewed 375 charts of women undergoing evaluation for LT from 2008[FIGURE DASH]2013 at Mayo Clinic Florida. We recorded demographics, Pap smear results, High risk HPV positive results, and co-morbid conditions. Univariate analysis was done to determine risk factors. We compared the result of the LT group to the general female population getting cervical cancer screening during the same time period. RESULTS: 37 of 375 (9.86%) LT patients had abnormal Pap smear, compared to 1784 of 26118 (6.83%) of the general population patients (p < 0.01). Among LT patients with cervical cytologic abnormalities, 40.5% were ASCUS, HPV positive (64.8% for non-LT patients), 29.7% were LSIL (28.1% for non-LT patients), 5.4% were HSIL (6.7% for non-LT patients) and 24.3% were cytology negative with HPV positive (0.2% for non-LT patients, p < 0.05). Younger age and presence of hypertension were associated with higher risk of having an abnormal cervical cytology or positive HPV status among LT patients. CONCLUSION: Patients undergoing evaluation for LT have increased prevalence of abnormal cervical cytology, or a positive High risk HPV test. Gynecologic surveillance for this high risk population is recommended.